Subcultura skinhead: una alternativa para el desarrollo de competencias ciudadanas (material de enseñanza) (2021)
In this work, a teaching material is made that allows the teacher to facilitate and implement classes in a more didactic and attractive way for the student, this focused on the development of citizenship skills through the identification of one of the subcultures of which little is known: Skinhead